La construction des paysages fluviaux urbains au Nord de la Méditerranée - Fanny Romain (Projets de Paysage)
The last couple of decades saw the resurgence of the river, which had previously “disappeared” from the urban scene (burried, canalized or used by several types of infrastructures), as a major part of the urban stage set. Even though its irregular flow used to prevent it from playing a similar role in North Mediterranean towns, the river has also become an important urban image there. The meanings and stakes of this landscape’s construction are the subject of a thesis, whose reasoning is displayed in this article. It is based on a comparative approach of two towns in the South of France – Perpignan and Montpellier, respectively crossed by the rivers Têt and Lez –, so as to estimate the relevance of such a model of evolution in North Mediterranean towns. The undergoing analysis is focused on both urban river practices and imaginaries, in order to highlight the cultural and urban functions which are nowadays given to the river.